Self-Esteem And Personal Self-Concept InPrimary School-Aged Children - Umrzakova Gulchexraxon Abdurasuljon kizi (Euro Asian Journal Publishing, 2025)
This article investigates the development of self-esteem and personal self-concept in primary school-aged children, emphasizing their psychological, educational, and social dimensions. Self-esteem and self-concept are fundamental components of personality formation during childhood, influencing not only academic performance but also interpersonal relationships and emotional well-being. At the primary school stage, children begin to form a clearer sense of who they are, how they evaluate themselves, and how they are perceived by others. These processes are shaped by family upbringing, peer interactions, cultural environment, and school experiences. Drawing on psychological theories of child development, including the works of Erikson, James, and Cooley, the study explores how children construct their self-image and develop self-assessment mechanisms in relation to success, failure, and social comparison. Special attention is given to the role of teachers and classroom practices, as encouragement, feedback, and social inclusion significantly influence the development of positive self-esteem. The article also addresses challenges such as low self-esteem, negative labeling, and peer rejection, which can hinder healthy personality development. The study concludes that fostering self-esteem and a coherent self-concept requires a balanced approach combining psychological understanding with supportive pedagogical strategies, ensuring that children grow into confident, socially responsible, and emotionally stable individuals
Keywords: self-concept; primary education; pedagogy